Isorenieratene interaction with human serum albumin: Multi-spectroscopic analyses and docking simulation. (30th August 2018) - Chen, Yashu; Zhou, Yufeng; Chen, Mo; Xie, Bijun; Yang, Jifang; Chen, Jigang; Sun, Zhida
Highlights: The interaction of aromatic isorenieratene and HSA were firstly investigated. Isorenieratene showed higher stability in blood than nonaromatic carotenoids. Fluorescent spectroscopy, FT-IR, SERS and docking simulation were performed. Abstract: Isorenierantene was reported to be an aromatic carotenoid and has become a food ingredient, mainly from smear cheese, which possesses special antioxidant ability and significant photoprotective effect. In this paper, the interaction of isorenieratene with human serum albumin (HSA) was explored and compared with that of nonaromatic carotenoids using multi-spectroscopic methods and docking simulations. The results suggested isorenieratene could bind to HSA through a static quenching mechanism. The binding processes were spontaneous and exothermic, and the binding between isorenieratene and HSA was mainly driven by hydrophobic forces and electrostatic attraction. Synchronous fluorescence spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, and surface-enhanced Raman scattering (SERS) experiments showed isorenieratene may change the secondary structure of HSA and the micro-environment of its amino acids. Additionally, isorenieratene showed higher stability during the binding process than did nonaromatic carotenoids. Docking simulation indicated isorenieratene may bind to HSA at site II.